Efecto de los sistemas de preparación de terreno forestal al final del turno en pino hibrido en el norte de Misiones = Effect of forest site preparation at end of turn in hybrid pine at north of Misiones - Von Wallis, Alejandra (2023)
Forest activity is one of the principal economy activities of Misiones, whit 405800 ha cultivated. Site preparation practices that include the management of forest harvest rests are seen as environmentally friendly. After periodic measuring the growth of an 18-year-old hybrid pine plantation with different site preparation systems that include soil tillage and conservation of forest harvest rest in the north of Misiones, through the diameter at breast height, it can be said that where the remnants of the harvest were conserved, the annual periodic increase of hybrid pine was greater than the increase of plantation whit tilled soil.